2015
DOI: 10.3109/17453674.2015.1053775
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative local infiltration anesthesia with ropivacaine has no effect on postoperative pain after total hip arthroplasty

Abstract: Background and purpose — The local infiltration analgesia (LIA) technique has been widely used to reduce opioid requirements and to improve postoperative mobilization following total hip arthroplasty (THA). However, the evidence for the efficacy of LIA in THA is not yet clear. We determined whether single-shot LIA in addition to a multimodal analgesic regimen would reduce acute postoperative pain and opioid requirements after THA.Patients and methods — 116 patients undergoing primary THA under spinal anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
2
37
0
2
Order By: Relevance
“…Meta-analysis of 5 studies [1114,16] with 361 patients after THA demonstrated that there was no significant difference of VAS score with activity between the PDI group and control group at 8 hours (MD 0.30, 95% CI −0.31 to 0.90, P  = 0.86; Table 3), 24 hours (MD 0.10, 95% CI −0.30 to 0.51, P  = 0.90; Table 3), and 48 hours postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analysis of 5 studies [1114,16] with 361 patients after THA demonstrated that there was no significant difference of VAS score with activity between the PDI group and control group at 8 hours (MD 0.30, 95% CI −0.31 to 0.90, P  = 0.86; Table 3), 24 hours (MD 0.10, 95% CI −0.30 to 0.51, P  = 0.90; Table 3), and 48 hours postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of 5 studies [9,11,13,14,16] with 367 patients after THA showed that the PDI group had less length of hospital stay (MD −0.47, 95% CI −0.64 to −0.29, P  < 0.00001; Table 3) than the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study by Hofstad et al the median pain score on mobilization on the first post operative day on a 10 point Likert scale, was about 4 (3-5). 13 Keeping the non-inferiority margin at 1.5 with alpha and beta errors at 5% and 20% respectively, the sample size needed minimum was 12 subjects in each arm. We decided to study 25 subjects in each arm.…”
Section: Discussionmentioning
confidence: 99%
“…It is legitimately inexpensive, technically uncomplicated, and may probably diminish postoperative embarrassment [24]. Perioperative localization anesthesia (LIA) is one of the ultimate techniques for accomplish these scopes [25][26][27]. LIA to the surgery site is a simple way and has demonstrated an immense impact on the abdomen, chest and plastic surgical setting.…”
Section: Painmentioning
confidence: 99%